2012
DOI: 10.1007/s00227-012-2056-9
|View full text |Cite
|
Sign up to set email alerts
|

Decreased pH does not alter metamorphosis but compromises juvenile calcification of the tube worm Hydroides elegans

Abstract: Using CO2 perturbation experiments, we examined the pre- and post-settlement growth responses of a dominant biofouling tubeworm (Hydroides elegans) to a range of pH. In three different experiments, embryos were reared to, or past, metamorphosis in seawater equilibrated to CO2 values of about 480 (control), 980, 1,480, and 2,300 μatm resulting in pH values of around 8.1 (control), 7.9, 7.7, and 7.5, respectively. These three decreased pH conditions did not affect either embryo or larval development, but both la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 73 publications
(124 reference statements)
0
33
0
Order By: Relevance
“…It was also confirmed that transition phases such as fertilization can be negatively impacted (Gonzalez-Bernat et al 2012;Lewis et al 2012). In contrast, larval metamorphosis into juveniles remained unaffected in echinoderms and annelids Lane et al 2012). Five studies showed that ocean acidification alone or in combination with temperature change can impact behavior in fish (Devine and Munday 2012;Munday et al 2012, but see Maneja et al 2012), mollusks (Schalkhausser et al 2012) and crustaceans (Zittier et al 2012).…”
Section: The Importance Of Relevant End Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also confirmed that transition phases such as fertilization can be negatively impacted (Gonzalez-Bernat et al 2012;Lewis et al 2012). In contrast, larval metamorphosis into juveniles remained unaffected in echinoderms and annelids Lane et al 2012). Five studies showed that ocean acidification alone or in combination with temperature change can impact behavior in fish (Devine and Munday 2012;Munday et al 2012, but see Maneja et al 2012), mollusks (Schalkhausser et al 2012) and crustaceans (Zittier et al 2012).…”
Section: The Importance Of Relevant End Pointsmentioning
confidence: 99%
“…These studies reported a range of responses. For example, it was shown that calcification can be strongly inhibited under ocean acidification (e.g., Lane et al 2012; Fig. 6a), but can also be stimulated leading to hyper-calcification (e.g., Dorey et al 2012).…”
Section: The Importance Of Relevant End Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have focused on the tropical species Hydroides elegans (Lane et al, 2013;Chan et al, 2012Chan et al, , 2013Mukherjee et al, 2013;Li et al, 2014). The results indicated reduced growth, increased porosity and reduced mechanical strength of the worm tubes, as well as increased mortality of larvae at lowered pH (< 7.9).…”
Section: Introductionmentioning
confidence: 99%
“…molluscs and crustaceans) (cf. [39][40][41]). Here using field transplant experiments, we looked for evidence of physiological acclimatization or adaptation in these species.…”
Section: Introductionmentioning
confidence: 99%